2016
DOI: 10.5505/epilepsi.2016.66487
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Findings of Epilepsy Patients who Underwent Follow-up at the Newly Established Clinic of the Muğla Sıtkı Koçman University Faculty of Medicine

Abstract: SummaryObjectives: The aim of the present study was to evaluate demographic and clinical findings of patients who underwent follow-up at the newly established epilepsy outpatient clinic of the Muğla University Faculty of Medicine. Methods:Included were 208 patients who underwent follow-up at the clinic between March 2014 and September 2015.Results: Mean age was 29.42±15.86, with a range of 5-84 years. Eighty-three patients were men (39.9%); 125 were women (60.1%). The most common risk factors included head tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Percentage of neonatal complications (7.5 %) took third place in our study. These results were similar with previous investigations (26)(27)(28).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Percentage of neonatal complications (7.5 %) took third place in our study. These results were similar with previous investigations (26)(27)(28).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the second common risk factor was history of febrile convulsions (21.4%) which is the most prevalent in studies from Sri Lanka and Iran (24,25). Additionally, two reports at tertiary clinics from Turkey revealed that febrile convulsions are the second risk factor in epileptic patients (26,27). Percentage of neonatal complications (7.5 %) took third place in our study.…”
Section: Discussionmentioning
confidence: 99%